2007
DOI: 10.1089/neu.2006.0099
|View full text |Cite
|
Sign up to set email alerts
|

Head Injury Mortality in the Nordic Countries

Abstract: Traumatic brain injury (TBI) is a major cause of morbidity and mortality in Western countries. Effective management planning for these patients requires knowledge of TBI epidemiology. The purpose of this study was to describe and analyze the development of TBI mortality in the Nordic countries during the period 1987-2001. Data on TBI deaths were retrieved from the national official statistical agencies according to specified diagnostic codes. We also collected data on the number of operations for acute TBI in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 36 publications
2
31
1
2
Order By: Relevance
“…Considering the distribution of age within our study population, a second peak was noted for the group between 50 and 59 years of age, but far less pronounced as compared to the younger age groups. In most other epidemiological studies on TBI, a second peak in the elderly, mostly due to falls, is observed [42] . As our approach within the given study was to analyze relevant TBI based upon prehospital emergency system documentation, minor to moderate falls in the elderly may have been missed.…”
Section: Discussionmentioning
confidence: 94%
“…Considering the distribution of age within our study population, a second peak was noted for the group between 50 and 59 years of age, but far less pronounced as compared to the younger age groups. In most other epidemiological studies on TBI, a second peak in the elderly, mostly due to falls, is observed [42] . As our approach within the given study was to analyze relevant TBI based upon prehospital emergency system documentation, minor to moderate falls in the elderly may have been missed.…”
Section: Discussionmentioning
confidence: 94%
“…A major drop in the mortality rate in the USA in trauma patients with severe TBI occurred between 1986 and 1995 [6]. The mortality rates from head injuries in Nordic countries (Denmark, Sweden and Norway) also declined from 1987 to 2000 [7], which is consistent with the trends in the USA [6]. However, a recent review by Stein et al [8] argued that TBI-related mortality has been stable over the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic brain injury (TBI) is a significant cause of morbidity and mortality in western countries with a mortality rate of 9.5–11.5/100,000 per year in Sweden, Norway and Denmark [1]. Each year, about 17,000 patients seek emergency care due to head injury in Sweden [2,3].…”
Section: Introductionmentioning
confidence: 99%